Pelatihan Teknologi Microsite sebagai Edukasi Pencegahan Stunting Dan Kemiskinan di Desa Tanah Putih Kecamatan Dulupi Kabupaten Boalemo - Anwar, Rustam; Mamuki, Emiliyan; R. Antu, Yulinda (LP2M IAIN Sultan Amai Gorontalo, 2025)
Community service activities in Tanah Putih Village aim to strengthen the village information system to improve understanding and education among health agents or cadres in the village, as they are the backbone of stunting and extreme poverty prevention through microsite-based digital technology training (mini web). The method used to achieve this goal includes internal training, community socialization, and mini web digital technology training (microsite). The results of community service activities in Tanah Putih Village, through digital technology training and socialization aimed at reducing stunting and extreme poverty, received a positive response from beneficiaries. In this case, the beneficiary families contributed to reducing and preventing stunting, while the beneficiary community worked towards reducing extreme poverty and aimed to develop this mini website into a large permanent website with the domain of the Tanah Putih Village government.